Chronology of stucco production in the Gulf and southern Mesopotamia in the early Islamic period - Lic, Agnieszka (Proceedings of the Seminar for Arabian Studies, 2017)
Although stucco is a challenging material to study, it proves to be useful for a researcher interested in Christian art in the Gulf and southern Mesopotamia. Comparative analyses of stucco decorations may contribute to a better understanding of the ecclesiastical and artistic relationships between particular sites, as well as revealing the chronological sequence of stucco production in the region. For example, a stucco panel from the site of al-QuΒūr on Failaka (Faylakā) Island, Kuwait, was most probably produced later than a small stucco plaque of similar design excavated at the church site on Сīr Banī Yās Island, UAE. Two other stucco fragments from al-QuΒūr are roughly contemporary with decorations from Christian sites in southern Mesopotamia. The relative dating of those stuccoes can be further correlated with the absolute dating of their sites of origin, which is based on radiocarbon analyses, studies of ceramic assemblages, and historical sources. The fact that the relative dating and the absolute dating coincide may support the dating of Сīr Banī Yās to between the late seventh and the second part of the eighth century, of al-QuΒūr to the eighth and early ninth centuries, and of some Christian sites in southern Mesopotamia also roughly to the eighth and early ninth centuries.